Analisis Masyarakat Konsumsi: Komodifikasi Jomblo Melalui Speed Dating - Intihaul Khiyaroh (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2021)
The definition of single is interpreted as a title that some people consider acurse for those who do not have a partner. In this era of digital development, global capitalism is using it to take advantage of the singles title by creating dating applications. The consumption style, which is guided by advertising in global capitalism, has in fact created a consumer society that consumes, which seems to be the "cash cow" of the capitalists. By visiting the application and then paying for dating fees and so on, it makes the singles as consumers who actually do not really need the application.